Analisis Kestabilan Lereng Tambang Di Area Penambangan Andesit PT.Mineral Sutera Pesisir Selatan Kabupaten Pesisir Selatan, Provinsi Sumatera Barat - Aprional Ifnanta; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. PT. MsPS is one of the companies engaged in the field of andesite mining located in Kampung Lubuk Rasan, District IV Jurai, Pesisir Selatan District, West Sumatra Province. Initial slope geometry has an overall slope height of 30 m with a slope of 50 and a single slope with a height of 10 m with a slope of 63. Clay data: Unit Weight (γ) = 15.97 kN / m3, Cohesion (c ') = 42.01 kN / m2 and inner shear angle (ϕ') = 40.36 °. Whereas with the method FK can obtain overall slope slope FK in saturated conditions of 0.573 and single slope in can FK slope in saturated conditions of 1,092.. Then the slope geometry was changed with a height of 30 meters with an overall slope of 31 and a single slope with a height of 7.5 m with an angle of 40 .Overall slope FK is obtained with an overall slope of 1,283 and single slope the 2,719 FK is obtained. By using the janbu method, the overall slope FK is obtained in the saturation condition of 1.095 and in a single slope the 2,575 slope after changing the geometry the slope using bishop method, the slope is safe.Keywords: initial geometry, simplified bishop, simplified janbu, safety factor.